PERBANYAKAN BIBIT JERUK SECARA IN-VITRO DAN BEBAS PENYAKIT CVPD - Wijayanto, Teguh; Taufik, Muhammad; Boer, Dirvamena; Suliartini, Ni Wayan Sri (Jurnal Agroteknos, 2011)
Abstract Citrus Vein  Phloem Degeneration (CVPD) is  one  of  the  most important diseases of citrus. Worldwide and national yield losses of citrus production due to this disease infection have been very significant.   This research ultimately aimed at producing citrus stocks through in-vitro culture, and free of CVPD.  Citrus seeds were used as explant and cultured on MS and WPM in-vitro media, supplemented with malt extract. Citrus plantlets were tested for the presence of  CVPD DNA using CVPD specific primers in PCR reactions.   Research results showed that MS basal medium supplemented with malt extract was quite good for in- vitro production of citrus plantlets. Plantlets were negative for CVPD infection based on PCR tests.  CVPD-free seedlings (Citrus reticulata) have been grafted with citrus rootstock (Citrus sinensis).  Grafted citrus seedlings were also proven to be negative for CVPD infection based on similar PCR tests.  Citrus seedlings/stocks produced by in-vitro culture, and free of CVPD, are now available for further growth. Keywords: Citrus Vein Phloem Degeneration (CVPD), in-vitro culture, PCR